Logística del proceso de exportación de banano de Asoguabo S.a. hacia el mercado de Bélgica. - Brito Tela, Genesis Nicole (My University, 2019)
The banana sector in Ecuador represents a significant item for the country's economy, climate conditions and favorable soils for the cultivation and harvesting of large volumes of bananas, which allows for a large supply for export to different markets international In Ecuador, the cultivation and harvest of this product are concentrated in several provinces, as well as in one of the most recognized organizations, in the province of El Oro, where the large suppliers are located, as well as the associations formed by small independent suppliers, which directly export their product. Nevertheless, the banana export process must follow a respective technical and customs process, which is why a correct management of the processing must be established. The objectives of this paper is the transport logistics and processing of the banana documentation of the Association of Small Producers Banana (ASOGUABO SA) to the market of Belgium in 2018, approach the legal, customs and administrative conditions to benefit from the regime of Definitive Export. For greater rigor of the theorist substantiation refers to information in the field, official sources, government websites, indexed journals and legal frameworks. Therefore, you can use a field research methodology, guide specialists and foreign trade actors.
El sector bananero en el Ecuador representa un significativo rubro para la economía del país, debido a que se dan las condiciones climáticas y de suelos favorables para el cultivo y cosecha a gran volumen del banano, lo que permite contar con una gran oferta para la exportación del mencionado producto hacia los diferentes mercados internacionales. En Ecuador, el cultivo y cosecha de este producto se concentra en varias provincias costeñas y una de las más reconocidas es la provincia de El Oro, en donde se encuentran grandes productores, así como también, asociaciones conformadas por pequeños productores independientes los cuales exportan directamente su producto. Sin embargo, el proceso de exportación de banano debe seguir un respectivo proceso técnico y aduanero por lo que se debe establecer una correcta gestión de tramitación. El presente trabajo tiene como finalidad determinar la logística de exportación y tramitación de documentación para el banano de la Asociación de Pequeños Productores Bananeros (ASOGUABO S.A.) hacia el mercado de Bélgica en el 2018, abordando las condiciones legales, aduaneras y administrativas para encajar en el régimen de Exportación Definitiva. Para mayor rigor de la fundamentación teórica se obtendrá información en campo, de fuentes oficiales, de páginas web gubernamentales, revistas indexadas y cuerpos legales. Por ello, se utilizará una metodología de investigación de campo, orientada a consultas a especialistas y actores del comercio exterior.
Keywords: EXPORTACIÓN; LOGÍSTICA; RÉGIMEN ADUANERO; COMPETITIVIDAD